Isochorismatase domain-containing protein 1 (ISOC1) participates in DNA damage repair and inflammation-related pathways to promote lung cancer development (2021)
Background: The advent of novel molecular targets has dramatically changed the treatment landscape of lung cancer in recent years. Isochorismatase domain-containing protein 1 (ISOC1) has been reported as a potential biomarker in gastrointestinal cancer, while its function in lung cancer has not been determined. Methods: The expression levels and prognostic significance of ISOC1 were assessed using bioinformatic analysis. Overexpression of ISOC1 and miR-4633, and knockdown of ISOC1 in non-small cell lung cáncer (NSCLC) cell lines were generated by lentiviral infection with overexpressed or shRNA plasmids. CRISPR/ Cas9 system was applied to knockout ISOC1 in A549 cells. The functions of ISOC1 and miR-4633 in lung cancer development were investigated using cell proliferation, migration, and invasion assays. Xenograft tumor growth assays in nude mice were further assessed the effect of ISOC1 in the tumorigenesis of NSCLC in vivo. Cell cycle distribution analysis was performed to uncover the underlying mechanism of ISOC1 and miR-4633 in promoting NSCLC cell proliferation. Co-immunoprecipitation combined with mass spectrometry and RNA sequencing were performed to uncover the potential mechanism of ISOC1 in lung cancer development. Results: Our results found that ISOC1 expression was upregulated in NSCLC tissues and that increased expression of ISOC1 was significantly associated with worse disease-free survival in NSCLC patients. Overexpression of ISOC1 could increase the proliferation, viability, migration, and invasion of NSCLC cells. Furthermore, miR-4633, located in the first intron of ISOC1, could also promote tumor cell progression and metastasis. Mice xenograft tumor assay showed that knockout of ISOC1 could significantly inhibit tumor growth in vivo. Besides, co-immunoprecipitation combined with mass spectrometry assay revealed that ISOC1 interacted with the proteins of DNA damage repair pathways and that upregulated ISOC1 expression could significantly increase the number of DNA damage lesions. RNA sequencing analysis showed that the downstream signaling pathways mediated by ISOC1 were mainly inflammation-related. Conclusions: We demonstrated that ISOC1 and its intronic miR-4633, both of them could promote NSCLC cell proliferation, migration, invasion, and cell cycle progression. ISOC1 participates in DNA damage repair and inflammation to promote lung cancer development.